2000
DOI: 10.1046/j.1365-2265.2000.00899.x
|View full text |Cite
|
Sign up to set email alerts
|

Application of a disease‐specific, quality‐of‐life measure (QoL‐AGHDA) in growth hormone‐deficient adults and a random population sample in Sweden: validation of the measure by Rasch analysis

Abstract: The Swedish QoL-AGHDA has good scaling properties, and hence can be considered a robust measure. It is suitable for assessing quality of life in adults with GH deficiency, and for making comparisons with adults who are not growth hormone deficient. Adult GH deficiency is associated with a significant impairment in QoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 35 publications
(59 reference statements)
5
61
2
Order By: Relevance
“…In a large European study, the expected score for the general population on the AGHDA scale was up to 3.3 for men and 4.6 for women (38), compared with the mean for a large series of hypopituitary patients of 7.1 (23), whereas in this series of patients with hypopituitarism due to craniopharyngioma the mean AGHDA score was considerably greater at 11.3. Notable factors that correlated with this poor score are the age at which the disease and the GHD developed and, in AO disease, the BMI and waist circumference. Although the CO group appeared to score better than the AO group, this was shown by multivariate analysis to be attributable to age; the NHP score was worse in the AO patients, consistent with the findings of an earlier study examining GHD of mixed aetiology (20).…”
Section: Discussionmentioning
confidence: 99%
“…In a large European study, the expected score for the general population on the AGHDA scale was up to 3.3 for men and 4.6 for women (38), compared with the mean for a large series of hypopituitary patients of 7.1 (23), whereas in this series of patients with hypopituitarism due to craniopharyngioma the mean AGHDA score was considerably greater at 11.3. Notable factors that correlated with this poor score are the age at which the disease and the GHD developed and, in AO disease, the BMI and waist circumference. Although the CO group appeared to score better than the AO group, this was shown by multivariate analysis to be attributable to age; the NHP score was worse in the AO patients, consistent with the findings of an earlier study examining GHD of mixed aetiology (20).…”
Section: Discussionmentioning
confidence: 99%
“…Social phobia is also more prevalent in COGHD adults than in short GH-replete adults (Nicholas et al 1997). Other studies have demonstrated impaired QoL in mixedonset GHD populations, which likely reflects decreased QoL in both AO and CO patients (Table 3) (Lynch et al 1994, Burman et al 1995, Wiren et al 2000. The reduced QoL in COGHD patients of normal height calls into question the use of increased height as an indicator of successful GH therapy.…”
Section: Gh Deficiencymentioning
confidence: 99%
“…Disease-specific measures, as expected, show a much greater impairment in GHD adults. For instance, a study using the AGHDA showed decreased QoL in a large cohort of untreated GHD patients (144) compared with 1448 normal adult controls (Wiren et al 2000). The increased sick leave and disability retirement in hypopituitary adults is also suggestive of a decreased QoL (Jonsson & Nilsson 2000).…”
Section: Gh Deficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…The population normative data for the QoL-AGHDA are available for the following countries: England and Wales (36)(37)(38), Spain (39), Sweden (37,40,41) and The Netherlands (37). The data for Belgium, France and Germany are in press.…”
Section: Qol-aghdamentioning
confidence: 99%